Pengaruh Implementasi Syariah Governance Terhadap Loyalitas Nasabah - Purnamasari, Intan; Darma, Emile Satia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
The research aims to examine and obtain empirical study on the effect of syariah governance implementation on customer loyalty. The object of this research is islamic banking in Yogzyakarta. Collecting data used purposive sampling method on islamic banking customers in Yogyakarta. A total of 102 respondents used as samples in this study. The analysis tool used is multiple regression with SPSS 15.0. Testing the quality of the data used in this research is a classic assumption test, while the hypothesis testing used the t test analysis method. The results of the research showed that fairness and syariah compliance has a positive significant effect on customer loyalty, while transparency, accountability, responsibility, and indepen-dency doesn't have positive significant effect on customer loyalty.